Participatory investigation of important animal health problems amongst the Turkana pastoralists: Relative incidence, impact on livelihoods and suggested interventions - Bett, Bernard K.; Jost, Christine; Mariner, Jeffrey C. (International Livestock Research Institute, 2008)
This report describes a study of the principal animal health problems in central and southern parts of Turkana South District, with particular emphasis on their relative importance, factors that promote their occurrence and persistence, and the perceived impact of intervention measures applied previously by the Turkana Livestock Development Program (TLDP). The study was conceived and supported by VSF Belgium, a non-governmental organization (NGO) which is implementing the TLDP. The first phase of the program was implemented between 2000 and 2005, and the second phase was initiated in 2006. The overall objective of the first phase, which occurred largely in Turkana Central (Turkwell, Loima and Kerio Divisions), was to improve the livelihoods of vulnerable pastoral communities through enhanced livestock production, increased access to water, improved marketing opportunities and peace building initiatives. The second phase of the program builds on the achievements of the TLDP I and seeks to expand the target area to include Turkana South (Kainuk, Katilu, Lokichar and Lokori Divisions). The study utilized participatory epidemiological techniques to capture and prioritize animal health problems observed in the target area. Topics of discussion include livestock species and benefits received from them; livestock diseases and interventions; effect of nomadic pastoralism on disease persistence and transmission; impacts of conflicts on livestock husbandry and disease occurrence and persistence; livestock species and disease priorities; disease control; access and utilization of veterinary inputs; community animal health workers; pastoralism and transboundary disease; and conflict and animal health care.